Increasing electricity generation by using Organic Rankine Cycles (ORC) through flue gas of boiler as heat sources - Rowshanaie, Omid; Mustapha, Saari; Ahmad, Kamarul Arifin; Rowshanaie, Hooman (International Engineering Science and Technology, 2014)
At the moment generating a large-scale electricity power from power plants especially thermodynamic cycles such as Organic Rankine Cycle (ORC) is becoming a controversial obstacle in related studies. In present ORC thermodynamic cycle, R245fa, NOVEC700, and R141b as refrigerant working fluids sent to a Heat Exchanger then sent to an Expander to produce electricity. Finally, the remaining working fluids are condensed by a Cooler and it is sent back to the ORC thermodynamic cycle. Current study is conducted and analyzed the net power output of Expander, the maximal net power output of ORC, the value of heat transfer between Fluegas to each working fluids at Heat Exchanger, the total heat transfer capacity (UA)total, and compare between the optimum pressure of working fluids at inlet of Expander and temperature of working fluids at inlet of Expander, which R141b has a highest amount compare with R245fa, and NOVEC7000. Whereas, with increasing the optimum pressure of working fluids at inlet of Expander, the temperature of working fluids at inlet of Expander is increasing slightly, because the optimum pressure of working fluids at inlet of Expander has a more effect on amount of electricity generated by Expander and as a result on the net power output of ORC.